Fractal Geometry Illustrated Left Atrial Appendage Morphology That Predicted Thrombosis and Stroke in Patients With Atrial Fibrillation - Lei, Chuxiang; Gao, Qi; Wei, Runjie; Li, Qijie; Liu, Xingli; Wu, Lingmin; Yao, Yan; Fan, Hongguang; Zheng, Zhe (Frontiers in Cardiovascular Medicine, 2022)
Background. This study aims to correlate the morphologic complexity of Left atrial appendage (LAA) with thrombosis and stroke in patients with atrial fibrillation (AF). Methods. The training cohort consisted of 46 AF patients (age 55.8 ± 7.2 years, 73.9% male) who were referred for radiofrequency catheter ablation. An independent validation cohort containing 443 AF patients was enrolled for further verification. All patients in training cohort underwent both transesophageal echocardiography (TEE) and enhanced computed tomography (CT). Fractal dimension (FD) analysis was performed to evaluate the morphological complexity of LAAs quantitatively. Clinical and imaging manifestations, FD of LAAs, and diagnostic accuracy were investigated and compared between AF patients in both training and validation cohort. Results. In the training cohort, LAAs (n=22) with thrombi had significantly higher FD than those without thrombi (n=24) (2.44 ± 0.07 vs 2.35 ± 0.11, P=0.003). ROC analysis suggested that the diagnostic accuracy of FD combined with a CHA2DS2-VaSc score was significantly higher than that of the CHA2DS2-VaSc score alone in AF patients with low to moderate risk (area under the curve: 0.8479 vs 0.6958, P=0.009). Similar results were observed in the validation cohort. Hemodynamic analysis revealed that LAAs with thrombi and high FD were prone to blood stasis and lower blood flow rate. Conclusions. LAA morphological complexity is closely associated with thrombosis and stroke in patients with paroxysmal AF. A new risk assessment system combining CHA2DS2-VaSc score and FD has a higher diagnostic accuracy in predicting LAA thrombosis.